Analysis of the Effect of Temperature Differences on Surface Hardness and FeB Diffusion Process on DIN 34CrNiMo6 Steel Material Through the Boriding Process - Umen Rumendi; Achmad Muhammad; Damarendro Hutomo Putro (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2020)
The availability of materials that meet production needs is sometimes not easy to obtain. Material properties must meet the standards are physical properties, including violence. One method is to increase the value of the surface hardness of the material by the boriding process. Boriding is a surface hardening process through the process of diffusion of the substrate, thereby causing the material hardness to increase. The results showed the temperature in the boriding process of DIN 34CrNiMo6 material was proven to affect the surface hardness of the material. The FeB diffusion process begins to form at temperatures of 850°C and 950°C. The optimal temperature for the boriding process is at a temperature of 950°C. Ketersediaan material yang memenuhi kebutuhan produksi terkadang tidak mudah untuk didapatkan. Sifat material harus memenuhi standar adalah sifat fisik material, diantaranya adalah kekerasan. Salah satu metode untuk meningkatkan nilai kekerasan permukaan material dengan proses boriding. Boriding merupakan suatu proses surface hardening melalui proses difusi terhadap substrat sehingga menyebabkan nilai kekerasan material tersebut mengalami kenaikan. Hasil penelitian menunjukkan temperatur pada proses boriding terhadap material DIN 34CrNiMo6 terbukti dapat mempengaruhi kekerasan permukaan material. Proses difusi FeB mulai terbentuk pada temperatur 850°C dan 950°C. Temperatur optimal untuk proses boriding adalah pada temperatur 950°C